The Implementation of Vocational Education Programs in Pondok Pesantren Al Qur'an Gumawang Wiradesa Pekalongan - Mahmudah, Siti; Fakhruddin, Fakhruddin; Rifai, Achmad (Educational Management, 2019)
This study aims to describe and analyze the planning, organizing, mobilization and supervision of vocational programs in PPAQ Gumawang. The research approach used is qualitative case study. The focus of research in this study is the implementation of a vocational education program aspects of planning, organizing, and monitoring of Data collected by interview, observation and documentation. Data validation was done by triangulation. Data analysis techniques used in this study is an interactive model. The results of this study were (1) vocational program planning begins with the identification of the needs of the program is the condition of the economic background of students the majority of the middle to lower, so can not directly get jobs because they can not go on to college. The aim is to set up a vocational program with semiskilled labor, program preparation done by forming the daily implementation team and make a financial plan; (2) organizing is done by dividing the task to the performer and the preparation of a program schedule; (3) guidance and motivation to do to move all the teachers and students involved in the program; (4) monitoring done by conducting supervision visits and attended follow-up classes. The conclusions of this research is the implementation of vocational education programs in PPAQ Gumawang done through the stages steps and procedures in accordance with the principles and functions of management.